EFEKTIVITAS PENGELOLAAN ARSIP DINAMIS DI DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA PEKANBARU - Erik Johan; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Science and technology are increasingly rapidly causing the need for information for every government organization and the private sector is an absolute matter. One that can be used as a source of information, namely archives, archives are records of information from an organization and individuals that are created along with the activities of the organization. Archives have a very important role in many aspects of life, apart from being a source of information, archives are also authentic evidence that can be justified. In this study, using qualitative methods using interview techniques, documentation, and observation. Researchers use Gibson's theory of effectiveness which divides effectiveness into five criteria, namely productivity, quality quality, efficiency, flexibility, and satisfaction. The management of dynamic archives is carried out by the Pekanbaru City Library and Archives Office. The purpose of this study was to determine the effectiveness of the management of dynamic archives at the Pekanbaru City Library and Archives Service. Management of dynamic records that is carried out has not been managed optimally, this is due to several factors that cause the effectiveness of managing dynamic archives at the Pekanbaru City Library and Archives Service is not optimal because human resources are considered insufficient to manage these dynamic archives and many still do not understand knowledge of dynamic archives, then insufficient facilities and infrastructure to support dynamic archive management activities.     Keywords: Effectiveness, Management, Dynamic Archives